TELAAH PUTUSAN INTERNATIONAL PEOPLE’S TRIBUNAL 65 ATAS PELANGGARAN HAM 1965 - M. Ali B., Indra Anugrah; Aisyah, Siti; Risal, M. Chaerul (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
In principle, human rights are regulated and upheld to protect human dignity and interests. The events of 1965 include past human rights violations that have not been resolved due to the neglect by the Indonesian government towards victims and their families. This study aims to examine the decision of the International People’s Tribunal 65 on human rights violations in 1965. The type of research used is library research with a normative approach. The results of the research show that the 65th Tragedy is a long history of major human rights violations committed by the Indonesian government that have not yet had a definite resolution. Acts of violations that included mass killings, imprisonment, enslavement, torture, forced disappearances, sexual violence, exile, false propaganda, involvement of other countries and genocide elicited various negative responses and criticism from various communities to provide protection and settlement for these crimes. The presence of the International People’s Tribunal Decision 65 has provided an illustration of the Indonesian government’s responsibility to investigate and provide appropriate punishment for the perpetrators of crimes and protection for victims in accordance with the applicable legal system. In addition, the Decision of the International People’s Tribunal 65 in an Islamic perspective as an instrument of Islah Islah in correcting and accounting for human rights crimes.